Tissue Homeostasis in the Wing Disc of Drosophila melanogaster: Immediate Response to Massive Damage during Development. - Herrera, S.C.; Martín, R.; Morata, G. (PLoS Genetics, 2013)
All organisms have developed mechanisms to respond to organ or tissue damage that may appear during development or during the adult life. This process of regeneration is a major long-standing problem in Developmental Biology. We are using the Drosophila melanogaster wing imaginal disc to study the response to major damage inflicted during development. Using the Gal4/UAS/Gal80(TS) conditional system, we have induced massive cell killing by forcing activity of the pro-apoptotic gene hid in two major regions of the disc as defined by Gal4 inserts in the genes rotund (rn) and spalt (sal). The procedure ensures that at the end of a 40-48 hrs of ablation period the great majority of the cells of the original Rn or Sal domains have been eliminated. The results indicate that the damage provokes an immediate response aimed to keep the integrity of the epithelium and to repair the region under ablation. This includes an increase in cell proliferation to compensate for the cell loss and the replacement of the dead cells by others from outside of the damaged area. The response is almost contemporaneous with the damage, so that at the end of the ablation period the targeted region is already reconstructed. We find that the proliferative response is largely systemic, as the number of cells in division increases all over the disc. Furthermore, our results indicate that the Dpp and Wg pathways are not specifically involved in the regenerative response, but that activity of the JNK pathway is necessary both inside and outside the ablated domain for its reconstruction.